The Iloilo Hotel, Restaurant and Resort Association (IHRRA) as an interest group its influence on the legislations of the Iloilo City government. - Herezo, Emily
This research project is a descriptive study on the influence of the Iloilo Hotel, Restaurant and Resort Association (IHRRA), as an interest group, on the legislation of the Iloilo City government . The study was conducted in the city of Iloilo where primary and secondary data were obtained. Interviews were done with respondents and written documents were gathered from the records of the IHRRA and the Sangguniang Panlungsod of Iloilo City. It was found that: (1) the IHRRA is not only confined to the protection of the interests and welfare of its members, but they are fully conscious of their responsibility in the economic and social progress of Iloilo City and of the country in general; (2) The interaction between the IHRRA and Iloilo City government was manifested through the various activities of the government where the IHRRA has participated in which are not only economic programs but also social and health programs; (3) members' interests on taxation, health and sanitation and the promotion and protection of their businesses are the ones functionally represented by the Association in relation with the Iloilo City government where City ordinances pertaining to these were mostly influenced; and (4) the concern on food security in terms of the availability of food supply was expressed by both the IHRRA and the Iloilo City government but their interaction was more on the sanitary aspect of food that are made available to the public. (p)Assessing the extent of influence of the Iloilo Hotel, Restaurant and Resort Association, as an interest group, on the legislations of the Iloilo City government, it can be said that the Association achieved significant results in pressuring the government. However, not all of its proposals were considered by the legislators for things were taken depending on their merits and demerits.